Comparison of STEM, non-STEM, and Mixed-Disciplines Pre-service Teachers’ Early Conceptions about Computational Thinking - HUANG, Wendy; LOOI, Chee-Kit; YETER, Ibrahim H (CTE-STEM 2022 conference, 2022)
This paper presents the results of an investigation on pre-service teacher' conceptions of computational thinking (CT) in Singapore prior to a two-hour introductory module on CT. Of 407 teachers, 280 provided valid responses to the pre-survey, which included questions on teachers' school subjects, current understandings of CT, confidence in their understandings of CT, and sources of the understandings. We deductively coded the open-ended responses through thematic analysis using four categories from a synthesis review on teachers' preconceptions of CT. The participants were classified into three groups, including STEM (primarily sciences and mathematics), non-STEM (e.g., humanities and languages), and mixed-disciplines (e.g., science and English language arts). The findings of the pre-survey showed that 42% of respondents (n=118) reported no prior knowledge of CT. Among the remaining 162 responses, the most popular view of CT was problem solving using various kinds of thinking, such as "logic", "abstraction", "step-by-step", and "decomposition" (n=106). STEM and mixed disciplines teachers (33%) reported higher levels of confidence compared to non-STEM teachers (15%). A higher percentage of STEM (64%) and mixed-disciplines (60%) pre-service teachers indicated learning about CT from formal courses during their university studies or teacher training, compared to non-STEM teachers (52%). This suggests that schools of education can play a bigger role in expanding CT awareness among pre-service teachers from non-STEM backgrounds. Finally, implications for teacher education are widely discussed.